The Application of The Healthy Stilt House Concept Based on The Local Wisdom of Bajo Etnic at Wuring Coastal Settlement in Maumere Town - Ambrosius A. K. S. Gobang; Yohanes Paulus P. Rangga; Marianus Yufrinalis; Ignasius Reynaldi Leo Loko (Universitas Muhammadiyah Surakarta, 2026)
The Wuring coastal settlement in Maumere City is inhabited by the Bajo community, characterized by traditional wooden stilt houses built over the sea and connected by plank and bamboo walkways, as well as several houses on land with concrete foundations and brick walls. However, increasingly complex environmental conditions and inadequate sanitation facilities have degraded the quality of the settlement. Frequently observed issues include the accumulation of plastic waste, household waste and sewage on the seabed during low tide. This research aims to examine the application of the healthy house concept based on Bajo local wisdom in the Wuring coastal area. The research employs a descriptive qualitative method with an ethnographic approach, utilizing comparative and empirical analysis through field observations, interviews and literature studies. The results indicate that aspects of Bajo local wisdom can be integrated with healthy house standards in spatial planning, facade openings, sanitation management and waste systems. The implementation of a healthy stilt house concept rooted in local wisdom can enhance the quality of the housing environment while preserving the cultural identity of the Bajo people.